2020
DOI: 10.1021/acsnano.0c03252
|View full text |Cite|
|
Sign up to set email alerts
|

Aerosol Filtration Efficiency of Common Fabrics Used in Respiratory Cloth Masks

Abstract: The emergence of a pandemic affecting the respiratory system can result in a significant demand for face masks. This includes the use of cloth masks by large sections of the public, as can be seen during the current global spread of COVID-19. However, there is limited knowledge available on the performance of various commonly available fabrics used in cloth masks. Importantly, there is a need to evaluate filtration efficiencies as a function of aerosol particulate sizes in the 10 nm to 10 μm range, which is pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
1,219
9
53

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 866 publications
(1,328 citation statements)
references
References 37 publications
47
1,219
9
53
Order By: Relevance
“…In both studies the filtration efficacy dropped significantly in the presence of leakage. 12 also found that in the presence of leakage, the efficacy of all masks decreased by about 50% or more.…”
Section: Effect Of Leakagementioning
confidence: 75%
See 3 more Smart Citations
“…In both studies the filtration efficacy dropped significantly in the presence of leakage. 12 also found that in the presence of leakage, the efficacy of all masks decreased by about 50% or more.…”
Section: Effect Of Leakagementioning
confidence: 75%
“…In some cases, the efficacy of cloth masks has been reported to be higher than 90%. In the study by Konda et al 12 double layered cotton with 600 threads per inch showed a filtration efficacy of 99.5 ± 0.1% in the >300 nm particle range compared to 99.9 ± 0.1% efficacy of N95 masks in the same range. Although less than the N95 masks in most cases such high efficiency of some types of cloth masks raises the hope of them being useful against droplet infections.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…As infected individuals release considerable numbers of submicron particles in the exhaled breath 15,16 , detailed measurements in this size range have also been reported 17,18 . These mostly include electrical mobility measurements for interpretation and methodology development [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%